Antibacterial and physicochemical properties of palm and olive-based wax esters / Mohammad Fawwaz Mazlan ... [et al.] - Mazlan, Mohammad Fawwaz; Mat Radzi, Salina; Abd Rahman, N. J.; Mohd Rehan, Maryam; Mohd Amin, Nor Amalina (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Palm-based and olive-based wax esters which are oleyl palmitate and oleyl oleate have been successfully synthesized using an esterification reaction. The products were verified using Fourier Transform Infrared (FTIR) and Nuclear Magnetic Resonance (NMR) spectroscopy to determine the presence of ester bond in their molecular structure. The synthesized wax esters were further analysed for their antibacterial activity against both Gram-positive and Gram-negative bacteria. In screening of an antibacterial activity, the agar diffusion test was employed. Minimum inhibition concentration (MIC) value was determined by microdilution method. The results showed that both Gram-positive bacteria, which are S. aureus and B. subtilis had high sensitivity toward oleyl oleate and oleyl palmitate. MBC (minimum bactericidal concentration) was determined to evaluate the antibacterial properties of both synthesized wax esters towards Gram-positive bacteria. Two antibacterial activities including bactericidal effects (killed the bacteria), or bacteriostatic effect (inhibit the bacterial growth) were determined by MBC value. Both wax esters possess a bactericidal effect towards all the Gram-positive bacteria studied. Finally, the physicochemical properties such as SPF value, peroxide value, saponification value and iodine value of both wax esters have been successfully determined and the data obtained suggest that the synthesized wax esters can be used as main ingredients in cosmetics formulation.